2020
DOI: 10.1108/lm-12-2019-0091
|View full text |Cite
|
Sign up to set email alerts
|

Public libraries in crisis time: empirigraphy of Iranian public libraries in the 2019 Iran massive flood

Abstract: PurposeOne of the largest floods in Iran happened in Nowruz in 2019, during which torrents of rain, flooding of rivers, landslides and the destruction of dams caused floods and led to financial losses and loss of life in 25 provinces of Iran. During and after the flood, 39 public libraries were closed, three libraries were evacuated and one was completely destroyed.Design/methodology/approachDespite the damage that occurred in the libraries, the preventive measures had been taken by many of them to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Crisis management seeks to reduce the impact of these unpredictable changes and is implemented through crisis detection, prevention and recovery, as well as design plans and procedures for crisis preparedness and implementation (Hazaa et al, 2021). A considerable number of studies on crisis in libraries have demonstrated the importance of crisis management and preparedness (Alajami, 2016; Green and Teper, 2006; Pazooki and Saboori, 2020). Formulating precise definitions is difficult and it is always possible to think of exceptions, but ‘crisis or disaster’ in libraries is defined as any incident which threatens human safety and/or damages or threatens to damage a library’s buildings, collections or items, equipment or systems (Eden and Matthews, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crisis management seeks to reduce the impact of these unpredictable changes and is implemented through crisis detection, prevention and recovery, as well as design plans and procedures for crisis preparedness and implementation (Hazaa et al, 2021). A considerable number of studies on crisis in libraries have demonstrated the importance of crisis management and preparedness (Alajami, 2016; Green and Teper, 2006; Pazooki and Saboori, 2020). Formulating precise definitions is difficult and it is always possible to think of exceptions, but ‘crisis or disaster’ in libraries is defined as any incident which threatens human safety and/or damages or threatens to damage a library’s buildings, collections or items, equipment or systems (Eden and Matthews, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our research focuses on the experiences of war-affected Ukrainians in order to develop recommendations on how information institutions can support them, as well as those affected by other man-made and natural disasters (Ethiopia Humanitarian Crisis, n.d.; Habib, 2022; Imray, 2023; Syria Situation, n.d.). Information institutions are recognized sources of support in the wake of disasters (Bishop and Veil, 2013; Patin, 2020; Pazooki and Saboori, 2021; Prestamo, 2018), and understanding the experiences of people directly affected by disasters is a necessary step in developing appropriate support infrastructure. This paper focuses specifically on the perspectives of Ukrainian parents of adolescents.…”
Section: Introductionmentioning
confidence: 99%